2008
DOI: 10.1186/1757-1626-1-109
|View full text |Cite
|
Sign up to set email alerts
|

Femoral-tibial-synostosis in a child with Roberts syndrome (Pseudothalidomide): a case report

Abstract: Background: Roberts syndrome (Pseudothalidomide) is a rare birth defect that causes severe bone malformation complex. The bones of the arms, and in some cases other appendages, may be extremely shortened and even absent. The fingers of the hands may be fused. An extreme case results in the absence of the upper bones of both the arms and legs so that the hands and feet appear attached directly to the body. This is called tetraphocomelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Literature reports of prenatal diagnosis of RS most frequently describe reduced fetal movements, restriction of fetal growth, and shortening of the long bones. 2,5,9,12,18,[20][21][22] In the case of prenatal diagnosis reported by Gollop et al, those findings were observed during a standard ultrasound at 21 weeks of gestation. 23 The clinical manifestations observed in our patient did not differ from the majority of RS cases described in the literature with RS (►Table 1).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Literature reports of prenatal diagnosis of RS most frequently describe reduced fetal movements, restriction of fetal growth, and shortening of the long bones. 2,5,9,12,18,[20][21][22] In the case of prenatal diagnosis reported by Gollop et al, those findings were observed during a standard ultrasound at 21 weeks of gestation. 23 The clinical manifestations observed in our patient did not differ from the majority of RS cases described in the literature with RS (►Table 1).…”
Section: Discussionmentioning
confidence: 83%
“…5,6 Herrmann et al also used, in 1969, the term "SC Phocomelia syndrome" or "thalidomide-like syndrome" (due to similarity of the clinical findings observed in patients exposed to thalidomide during pregnancy) in the description of two European families with clinical findings similar to RS. [7][8][9][10] Tomkins et al in 1979 described a cytogenetic alteration involving the centromere, which affected most of the chromosomes of RS patients, that was later called "premature separation of the centromere" by James German. 11,12 Furthermore, it was found that individuals with RS exhibit a lack of cohesion involving the heterochromatic region of some chromosomes, those around the centromere and in the distal portion of the Y chromosome long arm (called heterochromatin repulsion [HR]).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported on 17 patients with RBS who were treated with surgery ( Table I). The earliest surgeries that patients with RBS undergo are surgical cleft lip and palate repairs, which are initially performed when patients are 10 weeks of age (26). Cleft lips and palates have adverse effects on speech development, hearing, appearance, and psychology (27); therefore, it is necessary to correct these deformities.…”
Section: Surgical Treatment and Follow-up Of Rbsmentioning
confidence: 99%
“…Pseudo thalidomide syndrome [42] is also called Robert's syndrome is a rare genetic disorder characterized by disruption of cell division leading to malformation of the bones of skull, arms and legs. The child can be born with hypomelia, oligodactyly, syndactyly, clinodactyly, cleft lip, cleft palate and micrognathia.…”
Section: Miscellaneousmentioning
confidence: 99%